The influence of hip abductor weakness on frontal plane motion of the trunk and pelvis in patients with cerebral palsy - Krautwurst, Britta; Wolf, Sebastian Immanuel; Heitzmann, Daniel; Gantz, Simone; Braatz, Frank; Dreher, Thomas (Research in developmental disabilities, 2013)
Trendelenburg walking pattern is a common finding in various disorders, including cerebral palsy (CP), where it is seen in children and adults. Clinically, this deviation is viewed as a consequence of hip abductor weakness resulting in pelvic obliquity. Trunk lean to the ipsilateral side is a common compensatory mechanism to counteract pelvic obliquity and to maintain gait stability. However, no published investigations objectively address pelvic and trunk motions in the frontal plane or examine the correlation with hip abductor weakness in patients with CP. We selected 375 ambulatory (GMFCS I-III) patients with spastic bilateral CP and 24 healthy controls from our gait laboratory database. They had all undergone a standardized three-dimensional analysis of gait, including trunk motion, and a clinical examination including hip abductor strength testing. Selected frontal plane kinematic and kinetic parameters were investigated and statistically tested for correlation (Spearman rank) with hip abductor strength. Only a weak (r=0.278) yet highly significant correlation between trunk lean and hip abductor strength was found. Hip abductor weakness was accompanied by decreased hip abduction moment. However, no significant differences in pelvic position were found between the different strength groups, indicating that the pelvis remained stable regardless of the patients’ strength. Our findings indicate that weak hip abductors in patients with CP are accompanied by increased trunk lean to the ipsilateral side while pelvic position is preserved by this compensatory mechanism. However, since this correlation is weak, other factors influencing lateral trunk lean should be considered. In patients with severe weakness of the hip abductors compensatory trunk lean is no longer fully able to stabilize the pelvis, and frontal pelvic kinematics differs from normal during loading response. The results indicate that the stable pelvic position seems to be of greater importance than trunk position for patients with CP. Further studies are needed to investigate other factors influencing lateral trunk lean.
Gesehen am 27.10.2021